2017
DOI: 10.1016/j.pmedr.2016.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Social and emotional support as a protective factor against current depression among individuals with adverse childhood experiences

Abstract: Depression is one of the most prevalent mental health disorders among adults with adverse childhood experiences (ACE). Several studies have well documented the protective role of social support against depression in other populations. However, the impact of perceived social and emotional support (PSES) on current depression in a large community sample of adults with ACE has not been studied yet. This study tests the hypothesis that PSES is a protective factor against current depression among adults with ACE.Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(52 citation statements)
references
References 40 publications
7
45
0
Order By: Relevance
“…In the same vein, social support was a significant predictor of reductions in all symptoms of psychological distress, with the exception of anxiety‐related ones. Whereas these findings in part are in accordance with research on social support and mental health (Brinker & Cheruvu, ; Kleiman & Liu, ), we found differences in how perceived support versus social contact related to psychological distress. Notably, both forms of social support were important correlates of reductions in symptoms of interpersonal sensitivity.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the same vein, social support was a significant predictor of reductions in all symptoms of psychological distress, with the exception of anxiety‐related ones. Whereas these findings in part are in accordance with research on social support and mental health (Brinker & Cheruvu, ; Kleiman & Liu, ), we found differences in how perceived support versus social contact related to psychological distress. Notably, both forms of social support were important correlates of reductions in symptoms of interpersonal sensitivity.…”
Section: Discussionsupporting
confidence: 91%
“…There is extensive research documenting the importance of social support for mental health and specifically its protective role against the psychological sequelae of multiple stressors (Brinker & Cheruvu, ; Galea et al , ; Kleiman & Liu, ; Schwarzer & Knoll, ; Uchino, ). Conversely, social isolation, increasingly experienced among urban populations, is a well‐documented risk factor for psychological distress and related mental illnesses (Bennett, Gualtieri, & Kazmierczyk, ; Gruebner et al , ; Heinz, Deserno, & Reininghaus, ; Masi, Chen, Hawkley, & Cacioppo, ).…”
Section: Introductionmentioning
confidence: 99%
“…Patients who perceive empathy, compassion, and concern from healthcare professionals, including community health nurses, gain greater insight and motivation in addressing their health condition (Brooks, Lopez, Ranucci, Krumlaud & Wallen, ). Moreover, perceived emotional support helps patients cope with the disease (Brinker & Cheruvu, ) and address potential treatment barriers (van de Berg, Jansen‐Aaldring, Vries, & Hof, ). Hence, having a health professional who shows genuine compassion and concern with the health, emotional, and social plight experienced by patients with TB reassures them to continuously adhere with their treatment regimen.…”
Section: Discussionmentioning
confidence: 99%
“…High emotional support has been associated with higher survival in various clinical populations and is protective against stress, anxiety, and depression (Gordillo et al, 2009;Pilkington et al, 2015;Reblin and Uchino, 2008;Soler-Vila et al, 2003). Data from the Behavioral Risk Factor Surveillance System (BRFSS) found that individuals who reported high levels of perceived emotional support were 87% less likely to report current depression (Brinker and Cheruvu, 2017). Moreover, emotionally sustaining relationship experiences in early life impact an individual's health throughout the lifespan .…”
Section: Introductionmentioning
confidence: 99%